Algorithms and Devices for Noncoherent Digital Radio Signal Processing - Chernoyarov, Oleg V; Glushkov, Alexey N; Litvinenko, Vladimir P; Matveev, Boris V; Makarov, Alexander A (Engineering letters, 2020)
From a single point of view, there are presented the digital noncoherent algorithms and devices for detecting and demodulating radio signals. These algorithms are introduced as requiring the least possible number of simple arithmetic operations to be implemented because they are based on the basic fast algorithm for digital processing of narrowband signals. The devices are presented for detecting arbitrary narrow-band radio signals or phase shift keyed signals, demodulating amplitude shift keyed, frequency shift keyed or differential phase shift keyed signals as well as for demodulating the signals that are phase-shift keyed in toto. The characteristics of the specified devices are considered and their noise immunity in Gaussian noise is estimated. The theoretical results obtained are confirmed by computer simulation.